MANAJEMEN PENGELOLAAN KELAS MENURUT PARA AHLI - Kartini; Noviana, Fani; Selvia Manurung, Reni; Aulia Nisa, Putri (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2022)
In this day and age teachers are required to be more innovative in carrying out learning in the classroom, so that nowadays there are many various methods or ways of teachers in conveying learning. one of which the teacher must pay attention to is group teaching skills, where these skills lead to healthy and close interpersonal relationships between students with one another. So here more emphasis is placed on good cooperation to achieve effective and efficient learning goals in the present. And the research method that the author uses is a literature study approach, which is sourced from book references, and others. components of teaching skills in small groups and individuals, namely skills in holding a personal approach to each student, skills in organizing learning activities, skills in guiding and facilitating learning, and skills in designing and implementing learning activities